The effects of nominal maximum aggregate size on the properties of hot mix asphalt using gyratory compactor [compact disc] - 215038 Chong, Elizabeth Eu Mee (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2006